Implementasi Atika (Akses Terintegrasi Informasi Kesehatan Anestesi) sebagai Media Edukasi Perianestesi Berbasis Patient and Family Centered Care untuk Meningkatkan Pengetahuan Pasien dan Keluarga di RS TK II Udayana - Ratna Wardani; Putu Atika Parwati; I Wayan Sandiarta (Jurnal Pendidikan dan Pengabdian Masyarakat, 2026)
Perianesthesia education is essential for improving patient safety. However, a needs assessment at RS TK II Udayana identified gaps in the delivery of structured perianesthesia education. This program aimed to improve the knowledge of patients and families through the implementation of the ATIKA (Integrated Access to Anesthesia Health Information) method based on the Patient and Family Centered Care (PFCC) approach. A one-group pretest–posttest design was conducted involving 20 patients and their family members scheduled to undergo anesthesia. Educational interventions were delivered using PowerPoint, leaflets, and the ATIKA Digital Booklet. Participants knowledge was assessed using a structured questionnaire and analyzed with the Wilcoxon signed-rank test. The proportion of participants with good knowledge increased from 25% (n = 5) to 75% (n = 15), while poor knowledge decreased from 50% (n = 10) to 10% (n = 2). Statistical analysis showed a significant improvement in knowledge following the intervention (Z = −3.832; p < 0.001). The program also produced sustainable educational resources, including presentations, leaflets, and the ATIKA Digital Booklet. These findings indicate that the ATIKA method effectively enhances patient and family knowledge and supports the development of a structured, sustainable, patient- and family-centered perianesthesia education system.